POTENTIAL LASER PROCESSING PARAMETERS FOR OBTAINING MILK REPELLING SURFACE ON STAINLESS STEEL (AISI 316L) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2025)
In the previous authors review article it was confirmed, that the use of hydrophobic surfaces in the food industry is becoming more frequent, and new technologies for creating such surfaces are being developed. Among many available and developing technologies, further authors research is linked with laser radiation made hydrophobic surface on food grade stainless steel (AISI 316L). Many articles were found where researchers proved efficiency of laser made hydrophobic surface interaction with water, but none found where such surface interact with milk. Since milk is a water suspension of different substances (mostly animal fat and proteins), it is much complex fluid, that requires special handling for its processing and preserving. It follows from this, that milk has slightly different physical properties, that can affect its interaction with different hydrophobic surfaces. As no data was found about such interaction, this article main aim is to check free accessible laser processing parameters for obtaining water hydrophobic surface on stainless steel and find out if these parameters are usable for further research, but with milk. First experiments already have shown promising results and may be a start point for searching of most suitable laser processing parameters, in order to get most efficient milk repelling surface on stainless steel.